2016
DOI: 10.1007/s40257-016-0182-8
|View full text |Cite
|
Sign up to set email alerts
|

Laser and Light Treatments for Striae Distensae: A Comprehensive Review of the Literature

Abstract: Striae distensae (SD) are common dermatologic lesions that often arise as a result of rapid weight change, certain endocrine conditions, or prolonged exposure to steroids. SD initially present as raised edematous plaques (striae rubra), after which they become white and atrophic (striae alba) owing to local breakdown and reorganization of collagen and elastin. There currently exists no reliable treatment option, though numerous topical applications have been attempted. Lasers and light represent emerging nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 36 publications
0
55
0
3
Order By: Relevance
“…Pulsed dye laser results in textural improvements but has shown a limited benefit to treat striae alba (McDaniel et al, 1996). It may be beneficial in striae rubra by reducing erythema (Aldahan et al, 2016). Nd:YAG laser, also a vascular laser, demonstrated excellent improvement of up to 70% or more, even though it is specifically for immature striae rubra (Goldman et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Pulsed dye laser results in textural improvements but has shown a limited benefit to treat striae alba (McDaniel et al, 1996). It may be beneficial in striae rubra by reducing erythema (Aldahan et al, 2016). Nd:YAG laser, also a vascular laser, demonstrated excellent improvement of up to 70% or more, even though it is specifically for immature striae rubra (Goldman et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, white lesions seem very resistant to treatment attempts. 12 Topical management, like retinoic acid and chemical acid peels, shows very little evidence of efficacy with positive results limited to early stages of SD. 13,14 Different approaches like medical needling, resulting in micro trauma extending to the papillary dermis, believed to increase collagen and elastin production, or radiofrequency (RF) devices, delivering current to skin, converting into heat, subsequently leading to an increased collagen production, both showed small clinical improvements in SD albae.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have showed the advantages of non-ablative FP through involving minimal side effects and a quicker recovery [85][86][87][88][89][90][91], it should be noted that this technology is less effective than ablative resurfacing with CO 2 or Er:YAG lasers even if the treatment involves several procedures. Implementation of ablative fractional laser treatment leads to reduced recovery times after the procedure (compared to conventional treatment) as well as to a reduced risk of additional scarring and damaged pigmentation.…”
Section: Reviewsmentioning
confidence: 99%